What are you talking about? Applying cognitive interviewing to improve survey questions on women’s economic empowerment for market inclusion - Myers, Emily; Heckert, Jessica; Salazar, Elizabeth; Kalagho, Kenan; Salamba, Flora; Mzungu, Diston; Mswero, Grace; Adegbola, Patrice Ygué; Crinot, Geraud Fabrice; Kouton-Bognon, Baudelaire; Pereira, Audrey; Rubin, Deborah; et al. (International Food Policy Research Institute, 2023)
Monitoring progress toward women’s empowerment requires tools that reflect its underlying concepts. Cognitive interviewing is a qualitative approach for identifying sources of error in how respondents respond to survey items. This study identifies cognitive errors in survey modules included in the project level Women’s Empowerment in Agriculture Index for Market Inclusion (pro-WEAI+MI) in Benin and Malawi. Comprehension, retrieval, judgment, and response errors were all found to different degrees in the nine modules comprising the survey instrument. There are variations in findings by country context and, to a lesser extent, gender. The findings of this study informed revisions to the pro-WEAI+MI survey instrument and offer insights into how best to design survey modules used for monitoring progress toward gender equality in agricultural value chains and development efforts.